PENGGUNAAN SISTEM TEKNOLOGI INFORMASI DALAM LAYANAN KEUANGAN DAN AKUNTANSI PERUSAHAAN PT TELKOM INDONESIA (PERSERO) TBK DALAM KONDISI PANDEMI COVID-19 DI KOTA MEDAN - Muhammad Rifandy Perwanto; Mika Debora BR Barus; Rahima Boru Purba (Ensiklopedia Education Review, 2022)
: In Indonesia, remote work and work outside the company is common nowadays. Almost all companies have to virtualize faster by delegating their employees to work remotely, facing many challenges that they must overcome in a short period of time.This study aims to determine the direction and impact of changes in the digitization of financial accounting processes related to the COVID-19 pandemic. The level of use of financial accounting programs in remote work and improvement of work organization, availability of internet platforms, identification of data security levels, definition of barriers that affect the boundaries of the digitization process and financial accounting programs that have been created. The study took part of 236 respondent-entrepreneur accounting. The survey considered 27 used. Related survey questions: software used in financial accounting companies, changes in use during the pandemic, ways to secure personal data, implementing remote work, barriers to making changes in financial accounting processes. Respondents' results showed that 78% of companies gave them online access to finance and accounting programs. More use public facilities (56%) than private facilities (44%). It should also be noted that in half of the cases studied, 76-100% of the employees of the surveyed companies received financial and accounting data online.Keywords: Information Technology Systems, corporate finance and accounting programs, the COVID-19 pandemic